Risk of malignancy in patients with inflammatory bowel disease treated with Azathioprine or 6-mercaptopurine : the Cape Town experience - Setshedi, Mashiko (Department of Public Health and Family Medicine, 2014)
Includes bibliographical references (leaves 55-63).